Ex vivo culture of the intestinal epithelium: strategies and applications. Issue 8 (19th May 2014) - Leushacke, Marc; Barker, Nick
Abstract : Limited pools of resident adult stem cells are critical effectors of epithelial renewal in the intestine throughout life. Recently, significant progress has been made regarding the isolation and in vitro propagation of fetal and adult intestinal stem cells in mammals. It is now possible to generate ever-expanding, three-dimensional epithelial structures in culture that closely parallel the in vivo epithelium of the intestine. Growing such organotypic epithelium ex vivo facilitates a detailed description of endogenous niche factors or stem-cell characteristics, as they can be monitored in real time. Accordingly, this technology has already greatly contributed to our understanding of intestinal adult stem-cell renewal and differentiation. Transplanted organoids have also been proven to readily integrate into, and effect the long-term repair of, mouse colonic epithelia in vivo, establishing the organoid culture as a promising tool for adult stem cell/gene therapy. In another exciting development, novel genome-editing techniques have been successfully employed to functionally repair disease loci in cultured intestinal stem cells from human patients with a hereditary defect. It is anticipated that this technology will be instrumental in exploiting the regenerative medicine potential of human intestinal stem cells for treating human disorders in the intestinal tract and for creating near-physiological ex vivo models of human gastrointestinal disease.